The Glass House - Rahmanian, Hamid (Iran, 2008)
Verzio FF The fringes of Iranian society can be a lonely place, especially if you are a teenage girl with few resources to fall back on. The Glass House follows four girls striving to pull themselves out of the margins by attending a one-of-kind rehabilitation center in uptown Tehran. Forget about the Iran that you’ve seen before. With a virtually invisible camera, the girls of The Glass House take us on a never-before-seen tour of the underclass of Iran with their brave and defiant stories: Samira struggles to overcome forced drug addiction; Mitra harnesses abandonment into her creative writing; Sussan teeters on a dangerous ledge after years of sexual abuse; and Nazila burgeons out of her hatred with her blazing rap music. This documentary reflects a side of Iran few have access to or paid attention to: a society lost to its traditions with nothing meaningful to replace them and a group of courageous women working to instill a sense of empowerment and hope into the minds and lives of otherwise discarded teenage girls.